Breastfeeding initiation and duration and acute otitis media among children less than two years of age in Jordan: results from a case-control study - Furat K. AL-Nawaiseh; Madi T. Al-Jaghbir; Mohammad S. AL-Assaf; Hala K. AL-Nawaiseh; Majdi. M. Alzoubi (BMC, 2022)
Abstract Background Acute otitis media (AOM) is one of the most common infectious diseases that affects children. Breastfeeding has been linked to a lower risk of AOM in the first three years of childhood. The aim of this study was to identify the association between exclusive breastfeeding and the development of acute otitis media (AOM) and investigate the influence of breastfeeding duration on the presence of AOM. Methods In a retrospective case-control study, a sample of 98 children (cases) who were diagnosed with AOM and 98 children (controls) who were not diagnosed with AOM and were younger than two years old were selected from the Jordan University Hospital. Medical records were used to identify children with AOM. For both the case and control groups, the children's mothers completed a self-administered questionnaire about factors linked to the incidence of AOM.The type of feeding and the duration of breastfeeding were assessed using a validated questionnaire. Results The data indicated that among children who developed AOM, 23.5%were artificiallyfed, while 22.4% and 13.3% were exclusively breastfed for 3 months and 6 months, respectively. Approximately 70.7% of the children without AOM were exclusively breastfed for 6 months, compared with only 29.3% of the children without AOM who were exclusively breastfed for 3 months.Logistic regression revealed that nonexclusive breastfeeding, exclusive breastfeeding for 3 months, and exclusive breastfeeding for 6 months were protective factors against AOM (OR = 0.23, 0.18, and 0.25, respectively; P < 0.05). A short duration of exclusive breastfeeding was considered a risk factor for the development of AOM (OR = 1.7, P < 0.05). Conclusions The escalation of AOM is tightly connected to the early introduction of formula feeding in the first six months of life. Breastfeeding had a protective impact on the occurrence of AOM. Understanding factors that are associated with the occurrence of AOM in children may support the role of public health institutions and primary health care in the prevention and reduction of AOM episodes and the need for national health strategies to promote breastfeeding.